Sol-gel synthesis of novel Li-based boron oxides nanocomposite for photodegradation of azo-dye pollutant under UV light irradiation. (1st September 2019) - Ranjeh, Mahdi; Beshkar, Farshad; Salavati-Niasari, Masoud
Abstract: In the present study, Li2 B4 O7 /LiBO2 /Li3 BO3 (LBO) nanocomposites were synthesized by a modified Pechini sol-gel route utilizing the mixture of different polybasic acids and gelling agents. This work demonstrated that by controlling the reaction variables including kind of polybasic acids and gelling agents, pH and mole ratio of polybasic acid to total metals, the LBO nanostructures with various morphologies and particle sizes were prepared. Furthermore, the LBO nanocomposites showed excellent TOC removal (70%) and photocatalytic efficiency (91%) in order to photodegradation of acid violet 7 azo dye as water pollutant under UV light irradiation. Moreover, compared to commercial P25 photocatalyst, the LBO heterostructures exhibited higher photodegradation activity for removal of acid violet 7 dye in 90 min under UV light irradiation, even after four times cycles. The excellent photocatalytic degradation of LBO photocatalyst can be ascribed to the strong photon absorption, high-efficiency charge carrier separation, uniform particle size and appropriate band gap energy of the nanocomposite. Also, radical trapping capability test exhibited that the photoinduced superoxide radicals ( O2 − ) and holes (h + ) were the prevailing active species in the photocatalytic performance. Graphical abstract: Image 1 Highlights: Li2 B4 O7 /LiBO2 /Li3 BO3 nanocomposites have been successfully prepared by an improved Pechini approach. Effects of the various parameter on the morphology and particle size of products were examined. By controlling the synthetic conditions, different morphologies of the nanostructures were achieved. Photocatalytic efficiency for acid violet 7 azo dye under UV light irradiation was evaluated.